2015
DOI: 10.1002/2014jb011503
|View full text |Cite
|
Sign up to set email alerts
|

Gas migration into gas hydrate‐bearing sediments on the southern Hikurangi margin of New Zealand

Abstract: We present multichannel seismic data from New Zealand's Hikurangi subduction margin that show widespread evidence for gas migration into the field of gas hydrate stability. Gas migration along stratigraphic layers into the hydrate system manifests itself as highly reflective segments of dipping strata that originate at the base of hydrate stability and extend some distance toward the seafloor. The highly reflective segments exhibit the same polarity as the seafloor reflection, indicating that localized gas hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 63 publications
2
31
0
Order By: Relevance
“…The pronounced trend of predicted high gas hydrate concentration (trend I) along the principle deformation front of the Hikurangi Subduction Margin (Barnes et al, ; Figure ) is consistent with strong BSRs and gas related anomalies observed beneath deforming ridges along the margin (Crutchley et al, , , ; Henrys et al, ; Pecher et al, ; Figures and a) and increased velocities within the HSZ (Crutchley et al, , , ). Opouawe Bank, at the northeastern edge of our model (Figure ), is one of the most prominent and best studied ridges near the deformation front on this part of the margin.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…The pronounced trend of predicted high gas hydrate concentration (trend I) along the principle deformation front of the Hikurangi Subduction Margin (Barnes et al, ; Figure ) is consistent with strong BSRs and gas related anomalies observed beneath deforming ridges along the margin (Crutchley et al, , , ; Henrys et al, ; Pecher et al, ; Figures and a) and increased velocities within the HSZ (Crutchley et al, , , ). Opouawe Bank, at the northeastern edge of our model (Figure ), is one of the most prominent and best studied ridges near the deformation front on this part of the margin.…”
Section: Resultssupporting
confidence: 57%
“…Geochemistry, Geophysics, Geosystems 2010; Figures 9 and 10a) and increased velocities within the HSZ (Crutchley et al, 2015. Opouawe Bank, at the northeastern edge of our model (Figure 9), is one of the most prominent and best studied ridges near the deformation front on this part of the margin.…”
Section: 1029/2019gc008275mentioning
confidence: 71%
See 1 more Smart Citation
“…Approximately, 10% of natural hydrate occurs in coarse‐grained material (Boswell & Collett, ), which have favorable production characteristics (Boswell & Collett, ; Moridis et al, ; Yamamoto et al, ). Some of these reservoirs consist of thick, dipping, sand layers, bounded by low permeability material, that contain gas hydrate above and free gas below the hydrate stability zone (Boswell, Collett, et al, ; Boswell et al, ; Crutchley et al, ; Tréhu et al, ). Hydrate exists in these sand layers far above the base of hydrate stability at saturations ranging between 60 and 90% (Collett et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the finer sand used in the study of Hu et al (2012), the hydrate may cement grains and easily bridge across the pore space, and both of these modes have a greater impact on velocity. On the other hand, as we know, in the system of gas migration into gas hydrate-bearing sediments in field, the hydrate stability zone has high velocities, and the low-velocity zone is free gas-charged (Bunz and Mienert, 2004;Crutchley et al, 2015). And in the hydrocarbon leakage system, the low-velocity gas-charged zones always represent the leakage process (Løseth et al, 2009).…”
Section: Comparison Of Velocity Characteristics Between the Vertical mentioning
confidence: 99%